Differences in underlying cardiac substrate among S-ICD recipients and its impact on long-term device-related outcomes: real-world insights from the iSUSI registry - Gasperetti, Alessio; Schiavone, Marco; Milstein, Jenna; Compagnucci, Paolo; Vogler, Julia; Laredo, Mikael; Breitenstein, Alexander; Gulletta, Simone; Martinek, Martin; Casella, Michela; Kaiser, Lukas; Santini, Luca; et al. (Heart rhythm, 2024)
Background - Outcome comparisons among subcutaneous implantable cardioverter-defibrillator (S-ICD) recipients with nonischemic cardiomyopathies are scarce. - Objective - The aim of this study was to evaluate differences in device-related outcomes among S-ICD recipients with different structural substrates. - Methods - Patients enrolled in the i-SUSI (International SUbcutaneouS Implantable cardioverter defibrillator registry) project were grouped according to the underlying substrate (ischemic vs nonischemic) and subgrouped into dilated cardiomyopathy, hypertrophic cardiomyopathy, Brugada syndrome (BrS), arrhythmogenic right ventricular cardiomyopathy (ARVC). The main outcome of our study was to compare the rates of appropriate and inappropriate shocks and device-related complications. - Results - Among 1698 patients, the most common underlying substrate was ischemic (31.7%), followed by dilated cardiomyopathy (20.5%), BrS (10.8%), hypertrophic cardiomyopathy (8.5%), and ARVC (4.4%). S-ICD for primary prevention was more common in the nonischemic cohort (70.9% vs 65.4%; P = .037). Over a median (interquartile range) follow-up of 26.5 (12.6-42.8) months, no differences were observed in appropriate shocks between ischemic and nonischemic patients (4.8%/y vs 3.9%/y; log-rank, P = .282). ARVC (9.0%/y; hazard ratio [HR] 2.492; P = .001) and BrS (1.8%/y; HR 0.396; P = .008) constituted the groups with the highest and lowest rates of appropriate shocks, respectively. Device-related complications did not differ between groups (ischemic: 6.4%/y vs nonischemic: 6.1%/y; log-rank, P = .666), nor among underlying substrates (log-rank, P = .089). Nonischemic patients experienced higher rates of inappropriate shocks than did ischemic S-ICD recipients (4.4%/y vs 3.0%/y; log-rank, P = .043), with patients with ARVC (9.9%/y; P = .001) having the highest risk, even after controlling for confounders (adjusted HR 2.243; confidence interval 1.338-4.267; P = .002). - Conclusion - Most S-ICD recipients were primary prevention nonischemic cardiomyopathy patients. Among those, patients with ARVC tend to receive the most frequent appropriate and inappropriate shocks and patients with BrS the least frequent appropriate shocks.
Online verfügbar: 18 Januar 2024, Artikelversion: 28. März 2024
Gesehen am 28.01.2025
Mitlgieder der i-SUSI Investigators: A. Gasperetti, R. Arosio, M. Viecca, G.B. Forleo, M. Schiavone, C. Tondo, M. Ziacchi, I. Diemberger, A. Angeletti, M. Biffi, N. Fierro, S. Gulletta, P. Della Bella, G. Mitacchione.A. Curnis, P. Compagnucci, M. Casella, A. Dello Russo, L. Santini, C. Pignalberi, M. Magnocavallo, A. Piro, C. Lavalle, F. Picarelli, D. Ricciardi, E. Bressi, L. Calò, E. Montemerlo, G. Rovaris, S. De Bonis, A. Bisignani, G. Bisignani, G. Russo, E. Pisanò, P. Palmisano, F. Guarracini, F. Vitali, M. Bertini, J. Vogler, T. Fink, R. Tilz, F. Fastenrath, J. Kuschyk, L. Kaiser, S. Hakmi, M. Laredo, X. Waintraub, E. Gandjbakhch, N. Badenco, A. Breitenstein, A.M. Saguner, M. Martine, S. Seidl, L. Di Biase